PROFESSIONAL COMPETENCE TO PROVIDE FIRST AID : CURRENT SITUATION AND PROSPECTS OF FORMATION - Omelchuk, Mykhailo (Continuing Professional Education: Theory and Practice, 2019)
This article highlights the results of content analysis of curriculum and training programs for internship in «General pharmacy», in particular dedicated to the development on the theoretical basis for the possibility of self-differentiation of emergency conditions for further emergency treatment at them; the results of the survey of pharmacists, interns, regarding the formation of their competence in first aid; the expediency of updating the content of the training of pharmacists, interns, with priority issues of formation of competence in first aid (which was conducted among 46 respondents from among those who have successfully mastered this course «Assistance in emergency conditions and acute poisoning» in the unit «Clinical Pharmacy» by means of a questionnaire containing 19 closed questions); describes the results of a survey of interns-pharmacists on their first aid competence formation and found that the respondents did not have the full knowledge and skills to conduct basic resuscitation and often choose the wrong tactics in the event of sudden cardiac arrest; wrongly chosen measures to provide emergency assistance for patience with multiple trauma, not always determine the causes of the critical condition of the patient and correct non-pharmacotherapy used in emergency conditions; presents the features of training of pharmacists, which provides for the capture of significant amounts of information own pharmaceutical, chemical and pharmacognostical direction and determines simplified and shortened for the duration of their training cycle of basic medical sciences; described the necessity of amending the curriculum and training programs for pharmacists, including content updates and increase the duration of the course «Medical Emergency» for 12 hours, with an emphasis on mastering skills for first aid and first aid competence formation